Efektifitas Gerakan Tari Jaran Kepang Wonosobo Terhadap Perkembangan Motorik Kasar Anak di TK NU Al Madani - Anggun; Suci Ahiritunisa; Ahmad Khoiri (STAI Al-Amin Gersik Kediri Lombok Barat NTB, 2025)
This study aims to examine the effectiveness of the Jaran Kepang dance movements from Wonosobo in supporting the development of gross motor skills in early childhood children at TK NU Al Madani. Jaran Kepang dance, a traditional art form typical of Wonosobo, was chosen as a medium to develop gross motor skills such as balance, body coordination, agility, and dexterity. This research employs a descriptive method with an observational approach to class dance activities, along with interviews with teachers. The results of the study show that Jaran Kepang dance movements can significantly support the development of gross motor skills in children aged 5-6 years, with most children demonstrating progress in line with expectations.